2007
DOI: 10.1002/ptr.2176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α‐glucosidase and amylase by bartogenic acid isolated from Barringtonia racemosa Roxb. seeds

Abstract: Barringtonia racemosa presents a wide range of therapeutic applications. In the course of identifying bioactives from Indian medicinal plants it was observed that the hexane, ethanol and methanol extracts of B. racemosa seeds displayed potent yeast and intestinal alpha-glucosidase inhibitory activities. The methanol extract was found to be superior among them. However, none of the extracts exhibited pancreatic alpha-amylase inhibitory activity, rather the ethanol and methanol extracts accelerated the alpha-amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 21 publications
(23 reference statements)
3
55
0
Order By: Relevance
“…Mahera et al (2013) reported that the presence of stigmasterol-3-O-β-D-galactopyranoside and α-amyrin in mangrove plant of A. marina is responsible for its antidiabetic activity. Similarly, bartogenic acid in another mangrove plant Barringtonia racemosa was also found to possess α-glucosidase inhibition activity (Gowri et al 2007). Pentacyclictriterpenoids such as oleanolic acid, ursolic acid and lupeol found in mangrove plants such as A. marina and Sonneratia caseolaris also exhibited antidiabetic activities (Tiwari et al 2010;Mahera et al 2013).…”
Section: Saponins: Triterpenoid and Steroidal Glycosidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Mahera et al (2013) reported that the presence of stigmasterol-3-O-β-D-galactopyranoside and α-amyrin in mangrove plant of A. marina is responsible for its antidiabetic activity. Similarly, bartogenic acid in another mangrove plant Barringtonia racemosa was also found to possess α-glucosidase inhibition activity (Gowri et al 2007). Pentacyclictriterpenoids such as oleanolic acid, ursolic acid and lupeol found in mangrove plants such as A. marina and Sonneratia caseolaris also exhibited antidiabetic activities (Tiwari et al 2010;Mahera et al 2013).…”
Section: Saponins: Triterpenoid and Steroidal Glycosidesmentioning
confidence: 98%
“…The bark and the roots of the plant have been reported to possess different compounds such as 3,3 -dimethoxy ellagic acid, dihydromyticetin, gallic acid, bartogenic acid, stigmasterol, olean-18-en-3-β-O-ecoumaroylester and olean-18-en-3-β-O-Z-coumaroyl esters along with germanicol, germanicone, betulinic acid, lupeol, taraxerol, neo-clerodane type diterpenoids, nasimalun A and nasimalun B (Sun et al 2006;Yang et al 2006). The hexane, ethanol, methanol extracts of seeds of B. racemosa reported to possess α-glucosidase and α-amylase inhibition activities (Gowri et al 2007). Gowri et al (2009) also reported the presence of pentacyclic triterpenoid bartogenic acid in the methanol extracts of this plant responsible for its antidiabetic activity.…”
Section: B Racemosamentioning
confidence: 99%
“…One of the mechanisms by which these compounds may produce a blood glucose lowering response is their inhibitory effect on carbohydrate digestive enzymes, particularly on alpha-glucosidases (especially sucrase and maltase) and pancreatic alphaamylase (89, 111) (see Table 3). Although some studies have reported an interesting alpha-amylase inhibitory activity in addition to the most common alpha-glucosidase inhibitory effect (112,113), it is more common to find natural plants possessing stronger inhibitory activity against alpha-glucosidase than on alpha-amylase, which could be attributed to the different phytochemicals present (72,(114)(115)(116)(117)(118)(119)(120). In this sense, several studies have found a direct correlation between the amount of phenolic compounds in plant extracts and their capacity to inhibit carbohydrate digestive enzymes (19,25,89,92,112,121).…”
Section: Phenolic Phytochemicalsmentioning
confidence: 99%
“…General procedure for the preparation of benzimidazoles 3a-h To a stirred solution of o-phenylenediamine (1a, 1 mmol) and catalyst PdCl 2 (CH 3 CN) 2 (20 mol%) in anhydrous methanol (5 mL) was added a solution of carbonyl compound (2a, 1 mmol) under a nitrogen atmosphere over a period of 5 min at room temperature, and the contents were stirred at the same temperature for 4 h. After completion of the reaction (TLC), the solvent was removed under reduced pressure, and the crude product was subjected to column chromatography purification to afford 2- (2- In vitro -glucosidase inhibitory assay -Glucosidase inhibitory activities were determined as per earlier reported methods 18 , 19 . Rat intestinal acetone powder in normal saline (100: 1; w/v) was sonicated thoroughly and the supernatant was used as a source of crude intestinal -glucosidase after centrifugation.…”
mentioning
confidence: 99%